Prevalence of antibiotic-resistant bacterial strains in wastewater streams: molecular characterization and relative abundance - Fiaz, Marium; Ahmed, Iftikhar; Riaz, Rabaila; Nawaz, Uzma; Arshad, Muhammad (Folia microbiologica, 2021)
Bacteria from wastewater discharged to the sewerage near three hospitals of Islamabad, Rawalpindi, and Faisalabad were examined for resistance to the most commonly prescribed antibiotics in Pakistan. From the selected sites, a total of 109 isolates from 40 different species were identified based on 16S rRNA gene sequence and phylogeny. The isolates were tested for their resistance to ciprofloxacin, levofloxacin, ofloxacin, amoxicillin, and ampicillin. The results indicated that the isolates were resistant with the highest percentage to ampicillin and the lowest percentage to ciprofloxacin. Among the resistant isolates, 91.7% were found resistant to ampicillin, 83.5% to amoxicillin, 67.0% to ofloxacin, whereas only 27.5% to ciprofloxacin and 21.1% to levofloxacin. Among three sampled locations, the most of resistance was observed in Escherichia and Acinetobacter species. More than 30% isolated microorganisms were found resistant to more than three antibiotics. These findings concluded the presence of predominant microbial population resistant to antibiotics in wastewater channels near hospitals and its surroundings, which requires further investigation regarding their existence and spread in other environmental media having potential community health implications.
Keywords: Wastewater; RNA, Ribosomal, 16S; prevalence; Levofloxacin; Microbial Sensitivity Tests; Prevalence; mikrobiální testy citlivosti; antibakteriální látky; Anti-Bacterial Agents; Bacteria; levofloxacin; RNA ribozomální 16S; odpadní voda